Afmeting excl. passe-partout. . Titel prent: Schim van Dr. Kuyper, (neerziend op de 1 Mei-viering der arbeiders): Taai volk! - Hahn, Albert
Afmeting excl. passe-partout. Titel prent: Schim van Dr. Kuyper, (neerziend op de 1 Mei-viering der arbeiders): Taai volk!.